The General view of A Woman Concept and Female Job Titles - Ohunova Nozima Alisher kizi (Zien Journals, 2022)
Since the beginning of human history, motherhood has been regarded as the most sacred and permanent attribute in many cultures. Although the roles and responsibilities of women have changed over time, due to social, political and economic events, the main responsibility of women has always been perceived as "motherhood". With the modern era, women have participated in social spheres therefore, certain expectations and expectations about motherhood were formed in terms of one-sided views. Although motherhood has evolved over the centuries, the expectations of mothers reflect similar characteristics in almost all cultures. There are various studies based on the concept of "“woman”in psychology, anthropology and literature.In the following article,the concept “woman” will be analyzed widely socially and biologically.
Keywords: Cognition; feminine; suffix; dame